The home edit for teens : how to edit your space, express your style, and get things done! - Shearer, Clea, 1982-; Teplin, Joanna, 1979- (Clarkson Potter/Publishers, 2024)
"From the founders of The Home Edit comes a book for middle graders (3rd to 8th graders) teaching them how to keep every space of theirs organized-from the closet and under the bed to the desk, locker, bookbag, and more. Throughout will be engaging content-quizzes, checklists, and rainbowfied inspiration-to help kids create organizational systems and reach their room goals while expressing their budding points of view. The true promise: organizing and maintaining tidy spaces lead to a calmer, more confident kid"--